Cost-effective Integrated Harvesting of Short-Rotation Poplar Plantations - Spinelli, Raffaele (2020)
Small tree size represents the main challenge when designing a cost-effective harvesting system for European short-rotation plantations. This challenge is further complicated by the need to obtain 4-m logs for high-end products, which rules out the possibility to deploy whole-tree chipping. Both challenges can be met through mass handling, which must begin at the time of felling and continue uninterrupted along the whole supply chain. The authors designed and tested a simple system based on an excavator-based feller buncher, two farm tractors converted into grapple skidders and an excavator-based grapple saw adapted to operate as an impromptu slasher. This system proved capable of containing harvesting cost below 17 € per green ton, while matching the necessary work quality requirements, in terms of value recovery and log quality specifications. Furthermore, the whole system can be acquired with a limited capital investment, estimated at ca. 400,000 €. Being based on general purpose equipment, the system is also versatile enough for deployment in a number of alternative jobs, when the coppicing season is over.